IMPLEMENTASI SUPERVISI KLINIS DALAM PEMBELAJARAN FIQIH DI MADRASAH ALIYAH TARBIYATUL MUBTADIIN WILALUNG GAJAH DEMAK - Junadatul Munawaroh; Ruwandi Ruwandi (Universitas Islam Madura, 2023)
Clinical supervision is carried out by the teacher with the hope of creating conducive and memorable learning conditions. Learning that is too monotonous or teacher-centered makes children less enthusiastic. Therefore, this study has the following to find and analyze processes, constraints, and solutions to obstacles that arise in the implementation of clinical supervision. Researchers use a type of qualitative research. Data collection techniques through observation, interviews, and documentation. The validity of the data was obtained through a triangulation process, including triangulation of data, sources, techniques, and time. data analysis techniques through the process of data collection, data reduction, data display, then drawing conclusions and data verification. The findings in this study are: 1) the process of implementing clinical supervision with the aim of obtaining quality learning with indicators of suitability, attractiveness, effectiveness, efficiency, and learning productivity; 2) Obstacles experienced: teachers have difficulties formulating competency indicators, determining the right method, making minimal use of media, and evaluating properly; 3) solution: teachers are more active and diligent in participating in MGMP; supervisors provide motivation to teachers, consult with peer tutors, seek facilities and infrastructure, apply teacher discipline, and conduct staff evaluations. The implication of this research is that education managers will have a better understanding of the role and function of supervision in the successful implementation of education.